The Effect of Tokopedia E-Commerce Service Quality on Consumer Satisfaction in Accounting S1 Students Semester 1 Syarif Hidayatullah State Islamic University - iwan iraka; Muhammad Sabili Matin; Wahyunengsih Wahyunengsih (Shofanah Media Berkah, 2022)
− Abstract This study discusses the effect of Tokoppedia's E-Commerce Service Quality on Customer Satisfaction in the 1st semester of Accounting undergraduate students at Syarif Hidayatullah State Islamic University. This study has a problem formulation of whether service quality affects Tokopedia customer satisfaction. The purpose of this study was to determine whether there is an influence between service quality on customer satisfaction. This study uses quantitative methods with 2 variables, namely variable (x) Service Quality and variable (Y) Customer Satisfaction. The non-probability sampling technique used in this research sample is quota sampling. To analyze or process data using the latest version of SPSS 25. The methods used are validity analysis, reliability analysis, descriptive statistical analysis, normality analysis, and simple linear regression analysis. The results of this study indicate that all data are valid, reliable, and normally distributed. Service quality has a positive and significant effect on all indicators of variable X and variable Y. And there is an influence between service quality and customer satisfaction of 71.1%.